Hong Kong secondary students' self-regulated learning strategy use and English writing: Influences of motivational beliefs. (February 2021) - Bai, Barry; Wang, Jing
Abstract: This study aimed to examine the relationships between motivational beliefs, use of self-regulated learning (SRL) strategies, and competence in English as a second/foreign language (ESL/EFL) writing. The participants were 540 8th graders in Hong Kong. The motivational beliefs included growth mindset and perceived utility of writing that may play an important, yet unexamined role in Asian ESL/EFL learners' writing, as well as writing self-efficacy and interest that have received much attention. Multivariate analyses of variance (MANOVAs) were performed to examine whether the high, average, and low achieving writers differed in the level of motivational beliefs and SRL writing strategy use, respectively. Structural equation modeling (SEM) was conducted to examine the impacts of motivational beliefs on SRL writing strategy use. The results showed that the students had a high level of utility but a low level of interest in writing. They generally reported a high level of growth mindset and a low level of self-efficacy. The students of different writing competence levels differed in their motivation and SRL strategy use, indicating that both motivation and SRL ststrategy use contribute to writing competence. The results also showed that the students' motivational beliefs were crucial for SRL strategy use in English writing. The present study highlights the more important role of growth mindset and interest in comparison to self-efficacy and utility in Hong Kong ESL/EFL learners' writing. Implications for enhancing secondary school ESL/EFL learners' writing in an Asian context are discussed.